Bilateral Wrist Tenosynovitis owing to Acute Conversion of Adult T-Cell Leukemia-Lymphoma in a Patient with Rheumatoid Arthritis - Akira Hashimoto; Motoki Sonohata; Satomi Nagamine; Hiromu Yoshizato; Masaaki Mawatari (Case Reports in Orthopedics)
Human T-cell leukemia virus type 1- (HTLV-1-) associated arthritis is a relatively common disease. However, tenosynovitis owing to adult T-cell leukemia-lymphoma (ATL) is a rare condition. To the best of our knowledge, there have been no reports of tenosynovitis caused by conversion to acute ATL from one of the other ATL types. We present the case of a 60-year-old woman with rheumatoid arthritis (RA) with bilateral wrist tenosynovitis owing to the conversion to acute ATL from one of the other ATL types. She had swelling around the bilateral wrist joint under well controlled RA inflammation. She had no symptoms, physical findings, or laboratory findings indicative of conversion to acute ATL from one of the other ATL types. She underwent tenosynovectomy on the volar and dorsal sides of the left wrist joint to diagnose the cause of swelling around the bilateral wrist joint. Pathological analysis revealed diffuse proliferation of medium-sized atypical CD4(+) lymphocytes. Interestingly, she was diagnosed with wrist tenosynovitis caused by an acute ATL type. This diagnosis suggested that clinicians must consider ATL in connection with atypical wrist tenosynovitis in HTLV-1-endemic areas.